1982
DOI: 10.1021/jm00353a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and comparison of some cardiovascular properties of the stereoisomers of labetalol

Abstract: A useful method for the separation of labetalol into its two racemic diastereomers, as well as a stereoselective synthesis of its four stereoisomers, is described. The absolute stereochemistry of each isomer was determined by analysis of the DC spectra and confirmed by X-ray analysis. The alpha- and beta 1-adrenergic blocking properties, as well as the relative antihypertensive activities, have been measured in rats. The R,R isomer, 2a (SCH 19927), possesses virtually all of the beta 1-blocking activity elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…The 5,R-isomer possesses most of the a-blocking activity elicited by labetalol. Gold et al 15 concluded in their studies with labetalol that in determining the activity at both the a-and b-receptors, the absolute configuration at the chiral center bearing the methyl group plays a major role; only the diastereomers of labetalol having the (R)-configuration at the C-methyl center [ie, 7(R,R) and 7(S,R)] are significantly active at these receptors. The hemodynamic effects of labetalol and its (R,R)-isomer differ from those of most b-blockers (eg, propranolol) in that they did not reduce cardiac output or increase peripheral resistance.…”
Section: Pharmacodynamics and Electrophysiology Of Chiralitymentioning
confidence: 99%
“…The 5,R-isomer possesses most of the a-blocking activity elicited by labetalol. Gold et al 15 concluded in their studies with labetalol that in determining the activity at both the a-and b-receptors, the absolute configuration at the chiral center bearing the methyl group plays a major role; only the diastereomers of labetalol having the (R)-configuration at the C-methyl center [ie, 7(R,R) and 7(S,R)] are significantly active at these receptors. The hemodynamic effects of labetalol and its (R,R)-isomer differ from those of most b-blockers (eg, propranolol) in that they did not reduce cardiac output or increase peripheral resistance.…”
Section: Pharmacodynamics and Electrophysiology Of Chiralitymentioning
confidence: 99%
“…The present study compared the new antihypertensive drug dilevalol (an optical isomer of labetalol) 14 is against atenolol with respect to its effects on the central and major peripheral arteries (measured as pulse wave velocity) and on peripheral wave reflection (assessed from interpretation of pressure wave contour). …”
mentioning
confidence: 99%
“…Future studies will focus on its oral bioavailability and its persistence in the target tissue. In addition, since it has been shown by Gold et al [8] that the optically pure isomers of labetalol (an antihypertensive agent that is struc turally related to 143) have distinct pharma cological effects, stereospecific synthesis of the R,R and R,S isomers of 143 is underway to permit an investigation of the pharmaco logical properties of the individual diastereomers.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, 143 (i.v.) was shown to be more potent than ISO in the reduction of blood pressure in anesthetized rats [2][3][4][5], The ED50 values were found to be 1.44 X 10'9 mol/kg for 143 (0.78 pg/kg), 8.25 X 10'9 mol/kg for 119 (3.99 pg/kg), and 7.54 X 10-9 mol/kg for ISO (1.87 pg/ kg). Following intravenous administration to anesthetized dogs [4,5], the positive ino tropic response produced by 143 lasted 100 min, compared to the 2-3 min response observed with ISO at four times the molar dose.…”
Section: Introductionmentioning
confidence: 99%